Social Itinerary Recommendation from User-generated Digital Trails - Yoon, Hyoseok; Zheng, Yu; Xie, Xing; Woo, Woontack (Personal and Ubiquitous Computing, 2011)
Planning travel to unfamiliar regions is a difficult task for novice travelers. The burden can be eased if the resident of the area offers to help. In this paper, we propose a social itinerary recommendation by learning from multiple user-generated digital trails, such as GPS trajectories of residents and travel experts. In order to recommend satisfying itinerary to users, we present an itinerary model in terms of attributes extracted from user-generated GPS trajectories. On top of this itinerary model, we present a social itinerary recommendation framework to find and rank itinerary candidates.We evaluated the efficiency of our recommendation method against baseline algorithms with large user-generated GPS trajectories collected from Beijing, China. First, systematically generated user queries are used to compare the recommendation performance in the algorithmic level. Second, a user study involving current residents of Beijing is conducted to compare user perception and satisfaction on the recommended itinerary. Third, we compare mobile only approach with mobile + cloud architecture for practical mobile recommender deployment.